Environmental impact from space efficient dwellings - Can space efficient multi-family dwellings be beneficial to reduce the environmental impact from housing? - BERGLUND, ASTRID; Cederbom, David (My University, 2017)
Today Sweden has a great housing shortage leading to a demand of 710 000 new dwellings until the year 2025. At the same time the Swedish climate targets is to reduce the greenhouse gas emissions with 40 percent until the year 2020 and with 85 % until the year 2050 compared to the emissions the year 1990. The aim of this study is to examine if space efficient dwellings can be a beneficial option for housing when aiming to reach Sweden's climate goal. The purpose of the study is to define space efficient housing and to investigate the environmental impact from space efficient multi-family dwellings in relation to average size multi-family dwellings. To do this a study investigating the size of newly built dwellings has ben made and a life cycle assessment of two conceptual dwellings has ben performed. Space efficiency can be defined as a ratio of square meters per resident. With this definition, space efficiency can be calculated with the measure total floor area (BTA) per resident. From this study the recommendation is that space efficient dwellings have total floor area per resident lower than 41,5 square meters. According to this study the average size dwelling had 23-109 percent higher emissions per resident compared to the space efficient dwelling depending on impact category. This is partly due to the more residents per heated area, the lower the emissions from energy use per resident. It can also be explained with the fact that more residents per total floor area leads to lower emissions per resident from construction materials due to lower material use per resident. The greenhouse gas emissions per resident is 18,3 percent lower for space efficient multi-family dwellings in comparison to average size multi-family dwellings. Space efficient dwellings can hence be one part of the solution to lower the emissions from housing in the aim to reach Sweden’s climate target.
Keywords: Materialvetenskap; Byggnadsteknik; Materials Science; Building engineering